Modeling Temperature Fluctuations during Intermittent Water Usage within Water Systems: Water Quality Impact - Fatemeh Hatam; Catalina Ortiz; Marianne Grimard-Conea; Michèle Prévost (Engineering Proceedings)
Temperature is a crucial factor that can influence chemical and microbiological activities within building water systems. Due to factors like widespread water conservation programs or shutdowns resulting from events like the COVID-19 pandemic, water stagnation in these systems can escalate, impacting water temperature. By integrating EPANET-MSX with field data, this study seeks to simulate and analyze spatial and temporal fluctuations in water temperature and microbial growth resulting from temperature variations. The simulated temperature data and Legionella concentrations at three points are compared with field data during a period of three weeks. Overall, the modeled showerhead temperatures show good alignment with the monitored data, although underestimations occur in specific locations and time periods. The comparison between actual Legionella measurements and simulated concentrations, considering only temperature effects, demonstrates better alignment with field data for daily flushing showers. However, as stagnation increases, discrepancies between the modeled data and actual measurements suggest that other factors, such as available nutrients, may limit growth.